Neonatal multisystem inflammatory syndrome during acute SARS-CoV-2 infection - Jarić, Milica; Katić, Katarina; Djuretić, Andrea; Stojanović, Vesna; Milojković, Milica (Vojnosanitetski pregled, 2023)
.Introduction. During the development and spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic, a new inflammatory response syndrome arose in newborns, defined as the multisystem inflammatory syndrome (MIS) in neonates (MIS-N). Case report. A term infant girl with a fever diagnosed with SARS-CoV-2 infection was admitted to the hospital. In laboratory findings, the values of lactate dehydrogenase, ferritin, interleukin-6, and D-dimer were elevated. Upon admission, dual parenteral antibiotic therapy (ceftazidime, vancomycin), and one day later, low molecular weight heparin (LMWH) therapy, was commenced. After five days of hospitalization and febrility, with negative results of microbiological analyses and further deterioration of laboratory findings, intravenous immunoglobulin (IVIg) was administered at a dose of 2 g/kg for one day and methylprednisolone at a dose of 1 mg/kg/day for four days, after which the reduction of corticosteroid therapy was continued with prednisone. One day after IVIg dministration, the newborn became afebrile, with the gradual normalization of laboratory findings. The newborn was discharged after 16 days of hospitalization. Ten days after discharge, prednisone therapy was discontinued. Two weeks after discharge, the administration of heparin was discontinued. Seven days later, the D-dimer value increased significantly, and the anticoagulant therapy was reinstated. After one month, the D-dimer value completely normalized, and the LMWH therapy was discontinued. Conclusion. After the applied therapy for MIS in children, there was a cessation of febrility and gradual normalization of values of the laboratory parameters. This confirms that the newborn, in this case, probably had MIS-N. The prolonged elevated D-dimer value was most probably a consequence of the MIS.